ENCOURAGING EMPLOYEE’S INTRAPRENEURSHIP HABIT TO REDUCE CORRUPTION - Slamet Wahyudi (Politeknik Ubaya, 2019)
Indonesia recently ranked 96th for corruption index from 180 countries, means that still a lot of effort needed to reduce the number. The Imposing of laws for those who commit corruption and bribery have been implemented. Moreover, Government and Schools though people and student how to prevent it. Corruption becomes the main topic in everyday news. This paper tries to propose another action in order to reduce it namely Intrapreneurship. Intrapreneurship is similar to entrepreneurship, the first term refer to employees develops new business ideas for their companies within the company. On the other hand, Entrepreneurships defines as someone who starts up a new business with creativity to gain profit for better living using their own resources. This paper with design thinking method aims to find out some strategies how company could implement this program and at the end could reduce corruption.